Analisis Penerapan Kurikulum Merdeka Berbasis Direct Method Dalam Pembelajaran Bahasa Arab di SMP IT Al-Misbah Riau - Muhammad Rifaldi; Hendra Gunawan; Wahyuni Wahyuni (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This study aims to analyze the application of the Independent Curriculum based on direct method in Arabic language learning at SMPIT Al Misbah Riau. The Merdeka Curriculum emphasizes student-centered learning, flexibility, and strengthening communicative competence, which is in line with the principle of direct method that prioritizes the use of target languages directly without the intermediary of mother tongue. The research method used is a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects include Arabic teachers and students. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the application of the direct method within the framework of the Independent Curriculum is able to improve students' speaking skills (maharah kalam) and students' understanding of Arabic vocabulary and structure contextually. Teachers act as facilitators who actively create an Arabic-speaking environment in the classroom through the use of media, dialogue, and hands-on practice. However, there are several obstacles, such as the limitations of students' initial abilities, the lack of a supportive environment outside the classroom, and the need for continuous teacher training. Thus, the implementation of the Independent Curriculum based on the direct method is considered effective in improving the communicative competence of the Arabic language, although it requires the support of facilities, the environment, and the improvement of the quality of educator resources so that learning outcomes are more optimal.